2009
DOI: 10.1007/s00430-009-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide participation in granulomatous response induced by Paracoccidioides brasiliensis infection in mice

Abstract: The role of nitric oxide (NO) in granulomas of Paracoccidioides brasiliensis-infected inducible NO synthase-deficient C57BL/6 mice (iNOS KO) and their wild-type counterparts and its association with osteopontin (OPN) and matrix metalloproteinases (MMPs) was studied. At 15 days after infection (DAI), iNOS KO mice showed compact and necrotic granulomas with OPN+ macrophages and multinucleated giant cells, whereas wild-type mice developed loose granulomas with many fungi and OPN+ cells distributed throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
0
18
0
2
Order By: Relevance
“…and pro-cytokines involved in fibroblast activation and granuloma organization (e.g., pro-TNF-α and pro- TGF-β) [66], [67], [68]. In the intraperitoneal model of PCM using WT and iNOS −/− mice [69], NO production was associated with increased MMP9 activity and the loose organization of granulomas developed by WT mice. In the pulmonary model employed in the present study we suppose that the NO produced by the WT mice inhibited the production of TNF-α, which is required for granuloma organization, and of TGF-β, which is needed for tissue repair and Treg cell expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and pro-cytokines involved in fibroblast activation and granuloma organization (e.g., pro-TNF-α and pro- TGF-β) [66], [67], [68]. In the intraperitoneal model of PCM using WT and iNOS −/− mice [69], NO production was associated with increased MMP9 activity and the loose organization of granulomas developed by WT mice. In the pulmonary model employed in the present study we suppose that the NO produced by the WT mice inhibited the production of TNF-α, which is required for granuloma organization, and of TGF-β, which is needed for tissue repair and Treg cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β-induced Treg cell differentiation apparently contributed to the controlled tissue pathology even in the presence of the augmented immune response of the iNOS −/− mice. The study by Nishikako et al [69] revealed additional important information on the influence of NO in granuloma formation and disease outcome. At late stages of infection (120 days post-infection, not evaluated in our model), i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest osteopontin is a critical player in the formation of granulomas (18,26). Therefore, we investigated osteopontin in MWCNT-induced granulomas.…”
Section: Expression Of Osteopontin Mrna Is Up-regulated In Granulomatmentioning
confidence: 92%
“…36 Similarly, the production of nitric oxide (NO) by monocytes stimulated by P. brasiliensis seems to exert a negative modulatory effect on the formation of granulomas and a positive effect on fungal spread, leading to the dissemination of PCM. 37 Experimental studies in patients with PCM indicate that resistance to the fungus is dependent on activities of T Helper cells and macrophages/monocytes, mediated by IFN-γ and TNF-α. 27 The synergistic effect between these two cytokines is essential for host resistance and effective fungicidal activity against P. brasiliensis.…”
Section: Immunopathogenesis Of Pcmmentioning
confidence: 99%